Desempenho em Redes Horizontais de Cooperação no âmbito dos pequenos produtores de hortaliças: um estudo de caso sobre o PROJETO SEMENTE - CASSIA JESUINO MENDES (2022)
Small rural producers, especially vegetable producers, have faced significant challenges in the face of market demands and competition with larger and better capitalized producers. Aspects related to production scale, regularity of supply, diversity and quality of products are some of the main problems identified. Faced with these challenges, small vegetable producers have been looking for alternatives to distribution channels via medium and large retail, such as direct sales to the final consumer or via small retail establishments. In this context, collective action initiatives have been adopted for the development of production and marketing conditions for these producers, as is the case of horizontal cooperation networks. Although cooperative relationships provide significant benefits, studies also demonstrate the existence of flaws and problems. The main challenges that the networks face are related to the members' dissatisfaction with the performance, with the organization and structure of the network, as well as with the difficulties in the relationships between the participants of the cooperative arrangement. In view of this, the problem that is imposed refers to the difficulty of establishing a performance management system aimed at initiatives of horizontal cooperation networks, based on the diversity of interests. Therefore, this research aims to contribute to the process of developing horizontal networks of cooperation between small vegetable producers, by proposing indicators for a performance management system. To this end, this research, characterized as exploratory of a qualitative nature, adopted a Case Study as a method of procedure and Bibliographic Review techniques to obtain secondary data and interviews to obtain primary data referring to the case "Projeto Semente: Feira Agroecológica e Economia Criativa”, developed in Campo Grande/MS. From the identification, in the light of theory, of possible benefits acquired by participants of horizontal cooperation networks, confronted with the perceptions of benefits acquired by the vegetable producers of the Projeto Semente, it was possible to understand the need to consider indicators of different categories, namely: economic-financial, technical-operational, socio-behavioral and organizational. For each of these categories, suitable indicators were proposed for the specificities of small vegetable producers, in order to support the monitoring of the network's performance, both at the producer level and at the level of the network itself. In fact, the results showed that there are not many expectations of gains and that social benefits are as important as the economic-financial benefits, as well as the existence of a capable and committed coordinating agent.